Pengaruh Core Strengthening Exercise Terhadap Keseimbangan Statis Pada Anak Adhd Di Praktik Fisioterapi Wates Kediri - Purwati Purwati; Agung Hadi Endaryanto; Yohanes Deo Fau; Achmad Fariz (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: To determine whether core strengthening exercise has an effect on static balance in children with ADHD at Wates Physiotherapy, Kediri.Methods: This article used pre and post test experiments conducted on 15 pediatric patients with ADHD. The core strengthening exercise was carried out for 4 weeks with a meeting intensity of 12 times (3 times a week).Results: Core strengthening exercise in the first week had no significant effect on static balance with a significant value of 0.055>0.05. Meanwhile, at weeks 2 to 4, it showed a significant effect with a significant result of 0.001 at week 2 and 0.000 <0.05 at weeks 3 and 4.Conclusion: Core strengthening exercise has a significant effect on improving static balance in children with ADHD in a training period of more than 1 week (minimum 2 weeks to 4 weeks / 1 month). The average of static balance increase on 15 child with ADHD after 1 month of exercise seen from the stork test is 1,54.